Analysis of the Influence of Instagram Review, Destination Image and Tourist Attraction on the Interest of Highers Go to Mount Gede Pangrango National Park - Dudi Permana (Clean and Sustainable Production, 2023)
This study aims to analyze the influence of Instagram Review, Destination Image and Tourist Attraction Analysis on Interest of Climbers in Gunung Gede Pangrango National Park. The research design used by the author in this study uses causal research. To measure the variables, this study used a Likert scale. In this study, the research population is all people who have not, or have visited the Gunung Gede Pangrango National Park Tourism Object. Based on the number of the population that is not known with certainty, the sampling technique used is the Hair technique (2010) where the indicators are multiplied by 5 to 10. To collect data from various sources, this study uses a questionnaire data collection technique. The results showed that (1) Instagram Review had a positive and significant effect on the Visit Intention variable, (2) Destination Image had a positive and significant effect on the Visit Intention variable, and (3) Tourist Attraction has a positive and significant effect on the Visit Intention variable.